Quantum turbulence - Barenghi, C. F. (Cambridge University Press, 2024)
Turbulence plays a crucial role in contexts ranging from galaxy formation to heavy atomic nuclei, from jet engines to arterial blood flow, challenging engineers, physicists, and mathematicians. Recently, turbulence of quantum fluids displaying superfluidity has emerged as an exciting area of interdisciplinary research that spans fluid dynamics, low-temperature physics, and Bose-Einstein condensation. The first book on quantum turbulence, this work describes state-of-the-art results and techniques, stressing analogies and differences with classical turbulence. The authors focus in particular on low temperature phases of liquid helium, drawing on evidence from recent experiments, theory, and numerical simulations. Written by leading figures in the field, this is a go-to reference for students and researchers at all levels.